Penerapan Model Pembelajaran “Bedah Sastra” (BS) untuk Meningkatkan Pemahaman Budaya dan Nilai Sosial Generasi Z - Azzahra, Rizmada; Mattara, Wildan; Rohmah, Muttafaqur (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study analyzes the application of the "Literary Review" (BS) learning model in improving students' understanding of culture and social values. This model is implemented using a collection of short stories Warna Merdeka Kala Korona as teaching materials in the Indonesian Language subject at SMAN 1 Banyuwangi City. This study uses a qualitative approach with a case study method on 30 grade X students. Data were obtained through observation, analysis of student reflection documents, and class discussions. The results of the study indicate that the BS model improves students' understanding of social and cultural norms through exploration of literary works, contextual analysis, critical reflection, and application of values ​​in life. Students show active involvement, increased reading motivation, and higher social awareness. Although it requires more time and intensive mentoring, this model has proven effective in building students' characters who are empathetic, critical, and responsible.